Effects of lifestyle on men's health - Yafi, Faysal A.; Yafi, Natalie R. (Academic Press, an imprint of Elsevier, 2019)
Effects of Lifestyle on Men's Health provides an evidence-based review of the effects of modifiable risk factors such as sleep, diet, stress and exercise on various elements of men's health, notably sexual function, urinary function and cancer prevention and detection. Content highlights the most up-to-date basic and clinical information available, along with future research directions. Each chapter provides an easy to reference bullet point style summary to highlight the salient take-home messages from each section. Researchers and clinicians alike can use this book as a reference point for all matters related to lifestyle and men's health.